Avaliação da estabilidade e vida útil do queijo muçarela tipo pizza cheese durante o armazenamento - Viana, Letícia Fleury (2014)
For the production of cheese cheese type pizza some physical-chemical characteristics had to be changed, because the control of these characteristics benefit some properties, such as, cohesiveness, elasticity, hardness, non-enzymatic browning. In this work, the changes in physicochemical characteristics, proteolysis, texture properties, meltability, free oil, amount of blister and non-enzymatic darkening in the cheese were studied during the storage period of 120 Days. Fifteen cheese samples were collected in five consecutive weeks, three samples per collection. Physical and chemical analyzes were performed at zero times, 60 and 120 days of storage, and analyzes of proteolysis, texture, and functional properties were analyzed at times zero, 30, 60, 90 and 120 days of storage. The design was completely randomized. The averages were compared by the Tukey test at 5% probability. The pH decreased throughout the experiment period and was statistically different at all times. The acidity variable increased during the 120 days of study, however this increase was not statistically different between times 60 and 120 days of storage. The remaining variables did not differ statistically from one another during the experiment period. The chloride content is below that recommended by the literature during the 120 days of storage of cheese cheeses. The extent and depth index of proteolysis increased over time and were significantly different. The cohesiveness and elasticity decreased during the storage period of 120 days, this decrease being statistically different. The hardness increased during the studied period, this increase being different only from time zero to the time of 30 days. The chewability increased significantly up to 60 days and then decreased until the 120 time, and this did not present significant difference with the initial time (zero). With the converted data, in module, the adhesiveness increased during the 120 days of storage. The increase of the proteolysis during the storage period directly influenced the melting capacity, causing it to increase until the time of 90 days. The free oil released with the heating of the cheese during the pizza delivery is close to the minimum limits allowed by the literature. The amount of blister during the experiment increased significantly and could be considered above the literature standards since the zero time of the study. Luminosity values tended to white. The cheeses tended to be red in the values of h. Chroma values tended to be neutral. It is concluded that the milk used by the Southwestern dairy Goiano complies with the current legal standards and to what is recommended in the literature on the quality of the raw material for the production of cheese muzzarela for use in pizzas. The cheeses have physico-chemical characteristics that meet the legal requirements, except for the chlorides variable. The amount of fat and moisture meets the requirements for an ideal dough to be sold as pizza cheese.